Interaction of perfluorooctanoic acid with extracellular polymeric substances - role of protein - Yan, Wangwang (2022)
Perfluorooctanoic acid (PFOA) is nonbiodegradable, and adsorption is the main pathway for its removal in wastewater treatment plants (WWTPs). This study compared the capability of three types of sludge on adsorbing PFOA and investigated the role of extracellular polymeric substances (EPS) in the adsorption process. Results show that enhanced biological phosphorus removal (EBPR) sludge had the highest adsorption capacity for PFOA. Studies on the interaction between EPS and PFOA reveal that proteins play a crucial role in binding PFOA to EPS/sludge. Specifically, the aromatic and amide groups on the structure of protein can attract the C-F chains and carboxylic head of PFOA via hydrophobic interaction and electrostatic attraction, respectively. EPS of EBPR sludge has the highest amount of protein and binding sites, thus exhibits the highest adsorption capability for PFOA. This study reveals the interaction mechanism between PFOA and sludge EPS and provides new insight into the function of EPS in perfluoroalkyl substances removal in WWTPs.